2015
DOI: 10.1371/journal.pone.0122988
|View full text |Cite
|
Sign up to set email alerts
|

Relative Age Effects in Athletic Sprinting and Corrective Adjustments as a Solution for Their Removal

Abstract: Relative Age Effects (RAEs) refer to the selection and performance differentials between children and youth who are categorized in annual-age groups. In the context of Swiss 60m athletic sprinting, 7761 male athletes aged 8 – 15 years were analysed, with this study examining whether: (i) RAE prevalence changed across annual age groups and according to performance level (i.e., all athletes, Top 50%, 25% & 10%); (ii) whether the relationship between relative age and performance could be quantified, and correctiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
111
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(130 citation statements)
references
References 25 publications
(33 reference statements)
15
111
1
3
Order By: Relevance
“…Numerous solutions have been proposed to address RAEs, including rotating cut-off dates from year to year (Barnsley et al, 1985), longer (Grondin et al, 1984) or shorter agegroup bandwidths (Boucher & Halliwell, 1991), implementing player quotas/average age schemes (Barnsley & Thompson, 1988), physical classification schemes (Cumming, Lloyd, Oliver, Eisenmann, & Malina, 2017), and educating stakeholders regarding RAEs (Andronikos et al, 2015;Musch & Grondin, 2001). Specific to sprinting, Romann and Cobley (2015) have demonstrated how corrective adjustments could be applied to youth results to remove RAEs from top rankings, however additional research is required to determine if this strategy would work for other athletic disciplines. Furthermore, it is important to emphasise that relative age is a proxy measure for development, which is only accurate at the population level.…”
Section: Relative Age Effects In Youth Athletics 15mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous solutions have been proposed to address RAEs, including rotating cut-off dates from year to year (Barnsley et al, 1985), longer (Grondin et al, 1984) or shorter agegroup bandwidths (Boucher & Halliwell, 1991), implementing player quotas/average age schemes (Barnsley & Thompson, 1988), physical classification schemes (Cumming, Lloyd, Oliver, Eisenmann, & Malina, 2017), and educating stakeholders regarding RAEs (Andronikos et al, 2015;Musch & Grondin, 2001). Specific to sprinting, Romann and Cobley (2015) have demonstrated how corrective adjustments could be applied to youth results to remove RAEs from top rankings, however additional research is required to determine if this strategy would work for other athletic disciplines. Furthermore, it is important to emphasise that relative age is a proxy measure for development, which is only accurate at the population level.…”
Section: Relative Age Effects In Youth Athletics 15mentioning
confidence: 99%
“…In addition to age, a number of factors have been demonstrated to influence RAEs in track and field athletics. Two studies have investigated the effect of skill level on RAEs in track RELATIVE AGE EFFECTS IN YOUTH ATHLETICS 6 and field; Brazo-Sayavera et al (2016) examined athletes selected to Spanish national federation training camps, while Romann & Cobley (2015) divided athletes who had competed in the 60m sprint into groups on the basis of their seasonal best performance. In both cases, RAEs were higher when examining higher skill level athletes.…”
Section: Introductionmentioning
confidence: 99%
“…This system would be more fair, as every athlete would have the chance to be among the relatively older athletes at some point in the talent development process regardless of his or her birth month. Apart from these possible solutions, Romann and Cobley (2015) showed that relative age effects could be effectively removed in athletic sprints by using correction adjustments (linear regression analyses). As this proposal has not been investigated in a winter sport discipline so far, this should be done in future research.…”
Section: Anthropometric Characteristicmentioning
confidence: 99%
“…This is a particular problem in team sports where the indirect benefits of being older are widespread, because talent identification requires scouts or coaches to make subjective judgments of talent that are likely to be influenced by relative age (e.g., soccer, hockey and rugby, as opposed to objective measures such as time ran or distance jumped that can be used in individual sports, see Romann & Cobley, 2015). A number of practical suggestions have been put forward as possible interventions to minimise the selection-induced RAE in team sports, for instance by: rotating the age cut-off date for junior competition; altering the bandwidth of the age-groups; implementing quotas so that selected teams have an even representation of children of all birth-months; and grouping players according to their weight or height rather than age (Barnsley, Thompson, & Legault, 1992;Cobley et al, 2009;Helsen et al, 2012Helsen et al, , 1998Musch & Grondin, 2001).…”
Section: Introductionmentioning
confidence: 99%